Medición de la función esencial en salud pública N.º 11: Reducción del impacto de emergencias y desastres en salud en las direcciones de salud, 2019 - Bazán Vargas, Kieffer Segundo (Universidad Nacional Federico Villarreal, 2022)
Objective: To measure the performance profile of the essential function in public health No. 11: reduction of emergencies and disasters in health. Method: It is a basic and descriptive research, with a population and sample of 25 health departments in the country. The instrument used was a questionnaire adapted and defined by PAHO - WHO. Results: The performance profile was rated as "lower average performance" with a value of 0.41. The strengths identified were: coordination and alliances with other institutions and advice and technical support at the subregional levels and the weaknesses: management and development of standards and guidelines. The main areas to be strengthened are: response planning, assisted patient transport system, development and implementation of preparedness standards. The evaluation of the measurement years 2006 - 2019, at a global level, the performance profile of the EPHF 11 for the year 2006 had a percentage of 0.56, placing it in the "upper medium" performance quartile and for 2019 a "medium upper" performance profile. lower” with a 0.41. There is evidence of a decrease in the percentage of the performance profile by 0.15%. According to the ranking, the first place in performance is the Apurímac Health Directorate with 0.80. Conclusions: The FESP presents a decrease in its performance profile, which would lead the sector to strengthen its indicators.
Keywords: Funciones esenciales; Salud pública; https://purl.org/pe-repo/ocde/ford#5.00.00